Pelatihan Bahasa Inggris Bagi Pelaku Usaha Wisata Di Pantai Jikomalamo Kota Ternate - Ramis Rauf; Bakhtiar Majid (COMMENT: Journal of Community Empowerment, 2022)
English is one of the international languages whose speakers are widely spread, especially in the continent of Asia; Indonesia. Indonesia consists of thousands of large and small islands and has thousands of local languages . However, English is spoken chiefly by the Indonesian population. It is because English is one of the subjects that are not only taught in formal education but also course institutions. Tourism is a field of knowledge in the field of humanities. Tourism explores the problem of human needs for certain places that have exotic natural scenery/environments. Tourism also has a close relationship with tradition and culture. Tourism requires promotional tools to reach various groups from various parts of the world. One means of tourism promotion is through language. Therefore, it is not surprising that English is a means of tourism promotion.The use of English is very dominant in the tourism promotion sector and in terms of public services (hospitality), reservation of accommodation services, communication between (foreign) tourists and the public, promotion of goods and services, and several other fields. This service is carried out to determine the ability of tourism actors and tourism observers to promote tourism. In addition, training is also given to communicate in English for tourism actors who have not mastered English.